2016
DOI: 10.1186/s12917-017-0977-8
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and genomic rep-PCR fingerprints of Pseudomonas aeruginosa strains from animals on the background of the global population structure

Abstract: Background Pseudomonas aeruginosa is an important human opportunistic pathogen responsible for fatal nosocomial infections worldwide, and has emerged as a relevant animal pathogen. Treatment options are dramatically decreasing, due to antimicrobial resistance and the microorganism’s large versatile genome.Antimicrobial resistance profiles, serotype frequency and genomic profile of unrelated P. aeruginosa isolates of veterinary origin (n = 73), including domesticated, farm, zoo and wild animals mainly from Port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 42 publications
4
13
0
1
Order By: Relevance
“…isolates of Pseudomonas spp.. A total of 133 Pseudomonas spp. were isolated from 46 animal samples (6.5%) as follows (number of isolates): wild boars (57), mallards (30), ticks (17), farm animals (9), pets (10), rabbits (5), micromammals (3), and deer (2) ( Supplementary Table S1). These isolates were classified into the following species (number of isolates): P. aeruginosa (33), P. putida (23), P. fluorescens (17), Pseudomonas spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…isolates of Pseudomonas spp.. A total of 133 Pseudomonas spp. were isolated from 46 animal samples (6.5%) as follows (number of isolates): wild boars (57), mallards (30), ticks (17), farm animals (9), pets (10), rabbits (5), micromammals (3), and deer (2) ( Supplementary Table S1). These isolates were classified into the following species (number of isolates): P. aeruginosa (33), P. putida (23), P. fluorescens (17), Pseudomonas spp.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, those six exlA-positive strains produced more biofilm biomass (more than three times), phenazines, and motility (swimming and swarming) than the control PAO1 strain. On the other hand, the three remaining T3SS-positive P. aeruginosa strains were serotyped as O:6, one of the predominant serotypes in clinical and non-clinical strains 29,30 , and showed more biofilm biomass (range 146-166%) and motility, but lower phenazine pigment production than the PAO1 strain.…”
Section: Discussionmentioning
confidence: 99%
“…The P. aeruginosa isolate detected was from serotype O6, a predominant serotype commonly obtained from samples from several origins, including cystic fibrosis patients, human and animal diseases and the environment (Pirnay et al 2002(Pirnay et al , 2009. This isolate was included in another study (Serrano et al, 2017) in which it was concluded that animal P. aeruginosa population is homogeneously scattered and indistinguishable from the global population structure.…”
Section: Discussionmentioning
confidence: 99%
“…The oprI-positive isolates (n = 13) were then identified biochemically at species level using the Vitek 2 system (BioMerieux, Marcy-l'Etoile, France), and antibiotic resistance (ABR) profiling was performed using the same system in accordance with the manufacturer's instructions. Antibiotic compounds were tested as previously (Serrano et al, 2017) and were as follows: amikacin, aztreonam, cefepime, ceftazidime, ciprofloxacin, colistin, gentamicin, imipenem, meropenem, piperacillin + tazobactam, ticarcillin, ticarcillin + clavulanic acid, and tobramycin. Antibiotic resistance phenotypes, represented by the minimum inhibitory concentrations (MICs) were interpreted according to CLSI guidelines for Bacteria Isolated from Animals (CLSI, 2015a).…”
Section: Methodsmentioning
confidence: 99%
“…Our recently published research reveals that MRSA are common in the Portuguese animal communities (Coelho et al, 2011; Marinho et al, 2016) and that the environment and wild animals can be a reservoir or a vehicle of transport for MRSA (Sousa et al, 2017). Currently our research group is one of the few in Portugal that studies antibiotic resistance in wild animals (Oliveira et al, 2010; Clemente et al, 2015; Dias et al, 2015; Jones-Dias et al, 2016; Serrano et al, 2017). For example, we reported the first MRSA isolate of the CC398 ( spa -type t899) lineage from a wild animal in this country, recovered from a wild boar ( Sus scrofa ).…”
Section: Preliminary and Expected Resultsmentioning
confidence: 99%